Metaphoric way of thinking based on examples of the concept of ’sin’ - Ilona Lekhner; Lechner Ilona; Лехнер Ілона (Видавництво МДУ, 2019)
Abstract. The study deals in detail with the conceptualization process, the connection of the language, thinking and culture. A concept only has meaning to us if we have any experience with it. The conceptualisation of a concept can occur in our minds as a result of various cognitive processes, most of which can be traced back to our physical experiences. All of this contributes to the success of the interpretation of objects / events / concepts in our physical, social and cultural environment, that is, the creation of the meaning. These cognitive mechanisms, of course, do not function consciously andwithout them it would be impossible for us to interpret the entities of the world around us. The aim of conceptual processes is to help us build up our conceptual system and interpret new experiences to expand and change it. The study presents the main features of conceptual metaphor theory and emphasizes its important role in conceptualization. In the traditional sense, metaphors are categorized as poetic images and interpreted by literary writers. The function of metaphors is thus to achieve an artistic or rhetorical effect. According to the followers of cognitive language theory, the main task of the discipline is to describe the metaphor of natural language, since the conceptual metaphor is one of the basic tools of the conceptualization process. The study focuses on the parts of conceptual metaphors, the basics and types of metaphors, and the levels of metaphor research. One of the main statements of the theory is that abstract concepts can be understood by means of concrete concepts. This process is illustrated by the example of the term "sin". It demonstrates what cognitive model can develop in our minds and what specific concepts are involved in this process.
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008133
Keywords: conceptualization; conceptual metaphor; conceptual metaphor theory; abstract concepts